Keanekaragaman Gastropoda Sebagai Bioindikator Kualitas Perairan di Pantai Bangklangan Kabupaten Karangasem Bali - Sandewi, Dahlia; Watiniasih, Ni Luh; Pebriani, Dewa Ayu Angga (Current Trends in Aquatic Science, 2019)
This research was done at Bangklangan Beach, Perasi Village, Karangasem Regency, Bali. The purpose of this study was to determine diversity of Gastropods as bioindicator of water quality in Bangklangan Beach. Gastropods sampling was done by using a line transect technique stretched along 75 meters parallel to the shoreline. The size of the quadrant used is 1m × 1m. Result of research found 48 species Gastropoda joined in 14 Family. The density number of the gastropods in Bangklangan Beach was 218.25 ind/m2. The diversity index of the gastropods ranged from 2.21 to 2.83, the evenness index ranged from 0.76 to 0.78, the dominance index ranged from 0.11-0.18. The value of water quality in Bangklangan Beach such as water temperature ranged from 29.8?C-30.6?C, pH waters ranged from 8.3-8.4, dissolved oxygen ??ranged from 5.4-5.6 mg /l, water salinity ranged from 29.1-30.3 mg/l, water turbidity ranged from 1.25-1.64 NTU, BOD5 ranged from 7.54-8.69 and TSS ??ranged from 0.80-0.95 mg/l. Based on the correlation of temperature with H' has a very weak positive correlation with a value of 0.149, dissolved oxygen with H' has a very weak positive correlation with a value of 0.177, acidity with H' has a very weak negative correlation value of -0.236, salinity with H' has a weak negative correlation with a value of -0.459, turbidity with H' has a weak positive correlation with a value of 0.332, BOD5 with H' has a very weak positive correlation value with a value of 0.147. TSS with H' has a very weak positive correlation value of 0.013.